IMPLEMENTATION OF THE DECENTRALIZATION POLICY FOR EDUCATION AND DEVELOPMENT OF SPECIALISTS FOR HARKAMTIBMAS AT THE SPN POLDA SULUT - Sitorus, Bonar; Pengkey, Itje; Wawointana, Thelma (Retorika: Jurnal Komunikasi, Sosial dan Ilmu Politik, 2025)
The aim is to improve the competence of civil servants in the Indonesian National Police so that they have knowledge, leadership attitudes and technical skills.In Specialist Development Education. However, there are still problems in the Participant Determination Process, the Learning Process, and the technical implementation are still less than optimal. Therefore, a study was conducted entitled Implementation of the Decentralization Policy for Specialist Development Education at the North Sulawesi Regional Police SPN. This research is a qualitative method research, where data collection is carried out using interview methods, observation, documentation and other sources which aim to find out, describe, analyze and Decentralize Specialist Development Education at the SPN Polda Sulut based on the Chief of Police Regulation No. 14 of 2015. The research location is at the North Sulawesi Police State Police School and the North Sulawesi Police Human Resources Bureau. The research found that there were problems in the implementation of the selection of participants and the implementation of specialist development education at the North Sulawesi Regional Police's National Civil Service Agency (SPN Polda Sulut) due to communication and resource factors. Therefore, it is necessary to optimize the implementation of the Decentralized Specialist Development Education at the SPN Polda Sulut by gradually building coordination and communication, as well as fully decentralizing the program.